PERLINDUNGAN HUKUM BAGI DRIVER ONLINE AKIBAT ORDERAN FIKTIF DI TINJAU DARI UU NO. 13 TAHUN 2003 ( STUDI KASUS PT. MAXIM KOTA KENDARI ) - nengsi, widya; Diab, Ashadi L. (Fakultas Syariah IAIN Kendari, 2021)
In today's modern era, transportation is a form of implementation of community participation in the era of the industrial revolution 4.0 where in this case the community is spoiled with technology-based applications that provide services to people who will use transportation via smart phones. Through this application, consumers can place orders online, in which the details of the order are listed, such as driver data, pick-up location, destination, distance traveled, price and payment method. However, it turns out that the existence of online transportation can also harm online motorcycle taxi drivers, namely by cases of fictitious orders/false orders made by consumers with bad intentions. This study aims to find out how the form of legal protection for maxim drivers due to fictitious orders, and aims to find out how the legal review of the labor law for maxim drivers who are disadvantaged due to fictitious orders. The type of research used by the researcher is empirical research using a qualitative descriptive approach. The data sources used are primary data sources and secondary data sources. The results of this study indicate that the company PT. Maxim has provided protection for its drivers even though the form of protection is not in the form of compensation in the form of money, but the company provides protection in the form of preventive protection in the form of preventing the occurrence of fictitious orders by providing explanations and education as an effort to prevent the occurrence of fictitious orders. Meanwhile, repressive protection in the form of case settlement is by blocking accounts that have made fictitious orders so that drivers do not get orders from these accounts anymore. Judging from the labor law, protection for maxim drivers has actually been regulated in the Manpower Act because maxim drivers are workers and maxim are business actors. Keywords: Legal Protection, Maxim, Employment Act